2015
DOI: 10.1038/ncomms9470
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses reveal recurrent mutations in epigenetic modifiers and the JAK–STAT pathway in Sézary syndrome

Abstract: Sézary syndrome (SS) is an aggressive leukaemia of mature T cells with poor prognosis and limited options for targeted therapies. The comprehensive genetic alterations underlying the pathogenesis of SS are unknown. Here we integrate whole-genome sequencing (n=6), whole-exome sequencing (n=66) and array comparative genomic hybridization-based copy-number analysis (n=80) of primary SS samples. We identify previously unknown recurrent loss-of-function aberrations targeting members of the chromatin remodelling/his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
175
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(181 citation statements)
references
References 50 publications
4
175
1
1
Order By: Relevance
“…[20][21][22][23][24]53 Nonetheless, mutations in specific genes are variably recurrent in distinct entites, 24,25 and for a given gene, the distribution of the mutations and their relative prevalence are G869E E730K S520F S345F D1165G D1165H E1163K D342G R48W E47K PH1 PI heterogeneous. For instance, PLCG1 and CARD11 mutations are highly prevalent (up to 18% and 15% of the cases, respectively) in cutaneous T-cell lymphoma, in which conversely CD28 mutations are not found.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24]53 Nonetheless, mutations in specific genes are variably recurrent in distinct entites, 24,25 and for a given gene, the distribution of the mutations and their relative prevalence are G869E E730K S520F S345F D1165G D1165H E1163K D342G R48W E47K PH1 PI heterogeneous. For instance, PLCG1 and CARD11 mutations are highly prevalent (up to 18% and 15% of the cases, respectively) in cutaneous T-cell lymphoma, in which conversely CD28 mutations are not found.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on patient mutation sequencing analyses of various T-cell lymphoma subtypes frequently include the JAK/STAT pathway, where JAK1, JAK3, STAT3 , and STAT5B are predominantly mutated to cause hyperactivation [64,70,7578]. Importantly, ALK − ALCL is associated with STAT3 activation [64] and recurrent, somatic activating mutations in the closely related STAT5B gene were reported.…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%
“…Importantly, ALK − ALCL is associated with STAT3 activation [64] and recurrent, somatic activating mutations in the closely related STAT5B gene were reported. The STAT5B N642H mutation occurs with the highest frequency in PTCL, whereby most mutations cluster in the SH 2 and C-terminal transactivation domain [70,75,7882]. A recent study found that ~70% of T-PLL patients carry JAK-STAT hyperactivating mutations [70].…”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%
See 2 more Smart Citations